Organic–inorganic halide perovskite/crystalline silicon four-terminal tandem solar cells. Issue 3 (1st December 2014) - Löper, Philipp; Moon, Soo-Jin; Martín de Nicolas, Sílvia; Niesen, Bjoern; Ledinsky, Martin; Nicolay, Sylvain; Bailat, Julien; Yum, Jun-Ho; De Wolf, Stefaan; Ballif, Christophe
Abstract : We present a four-terminal perovskite/c-Si solar cell based on a CH3 NH3 PbI3 top cell with MoO x /ITO transparent hole contact. Abstract : Tandem solar cells constructed from a crystalline silicon (c-Si) bottom cell and a low-cost top cell offer a promising way to ensure long-term price reductions of photovoltaic modules. We present a four-terminal tandem solar cell consisting of a methyl ammonium lead triiodide (CH3 NH3 PbI3 ) top cell and a c-Si heterojunction bottom cell. The CH3 NH3 PbI3 top cell exhibits broad-band transparency owing to its design free of metallic components and yields a transmittance of >55% in the near-infrared spectral region. This allows the generation of a short-circuit current density of 13.7 mA cm −2 in the bottom cell. The four-terminal tandem solar cell yields an efficiency of 13.4% (top cell: 6.2%, bottom cell: 7.2%), which is a gain of 1.8%abs with respect to the reference single-junction CH3 NH3 PbI3 solar cell with metal back contact. We employ the four-terminal tandem solar cell for a detailed investigation of the optical losses and to derive guidelines for further efficiency improvements. Based on a power loss analysis, we estimate that tandem efficiencies of ∼28% are attainable using an optically optimized system based on current technology, whereas a fully optimized, ultimate device with matched current could yield up to 31.6%.